An analysis of observer‐rated functional vision in patients implanted with the Argus II Retinal Prosthesis System at three years. (24th January 2016) - Geruschat, Duane R; Richards, Thomas P; Arditi, Aries; da Cruz, Lyndon; Dagnelie, Gislin; Dorn, Jessy D; Duncan, Jacque L; Ho, Allen C; Olmos de Koo, Lisa C; Sahel, José‐Alain; Stanga, Paulo E; Thumann, Gabriele; et al.
Abstract: Objective: The purpose of this analysis was to compare observer‐rated tasks in patients implanted with the Argus II Retinal Prosthesis System, when the device is ON versus OFF. Methods: The Functional Low‐Vision Observer Rated Assessment (FLORA) instrument was administered to 26 blind patients implanted with the Argus II Retinal Prosthesis System at a mean follow‐up of 36 months. FLORA is a multi‐component instrument that consists in part of observer‐rated assessment of 35 tasks completed with the device ON versus OFF. The ease with which a patient completes a task is scored using a four‐point scale, ranging from easy (score of 1) to impossible (score of 4). The tasks are evaluated individually and organised into four discrete domains, including 'Visual orientation', 'Visual mobility', 'Daily life and 'Interaction with others'. Results: Twenty‐six patients completed each of the 35 tasks. Overall, 24 out of 35 tasks (69 per cent) were statistically significantly easier to achieve with the device ON versus OFF. In each of the four domains, patients' performances were significantly better (p < 0.05) with the device ON versus OFF, ranging from 19 to 38 per cent improvement. Conclusion: Patients with an Argus II Retinal Prosthesis implanted for 18 to 44 months (mean 36 months), demonstrated significantly improved completion of vision‐related tasks with the device ON versus OFF.